178k views
2 votes
write an equation of s circle with a radius of a circle with an equation of (x- 6)² + (y + 3)² =r² and containing (4, 1)

User Vitall
by
5.1k points

1 Answer

6 votes

We have the circle equation


(x-6)^2+(y+3)^2=r^2

We will find the radius r by substituting the given point, which belongs to the circle, that is,


(4-6)^2+(1+3)^2=r^2

which gives


\begin{gathered} (-2)^2+4^2=r^2 \\ 4+16=r^2 \\ 20=r^2 \end{gathered}

Then, the circle equation is


(x-6)^2+(y+3)^2=20

User UiUx
by
5.2k points